Frequency‐Agile Temporal Terahertz Metamaterials. Issue 12 (8th April 2020) - Pitchappa, Prakash; Kumar, Abhishek; Liang, Haidong; Prakash, Saurav; Wang, Nan; Bettiol, Andrew A.; Venkatesan, Thirumalai; Lee, Chengkuo; Singh, Ranjan
Abstract: Spatiotemporal manipulation of electromagnetic waves has recently enabled a plethora of exotic optical functionalities, such as non‐reciprocity, dynamic wavefront control, unidirectional transmission, linear frequency conversion, and electromagnetic Doppler cloak. Here, an additional dimension is introduced for advanced manipulation of terahertz waves in the space‐time, and frequency domains through integration of spatially reconfigurable microelectromechanical systems and photoresponsive material into metamaterials. A large and continuous frequency agility is achieved through movable microcantilevers. The ultrafast resonance modulation occurs upon photoexcitation of ion‐irradiated silicon substrate that hosts the microcantilever metamaterial. The fabricated metamaterial switches in 400 ps and provides large spectral tunability of 250 GHz with 100% resonance modulation at each frequency. The integration of perfectly complementing technologies of microelectromechanical systems, femtosecond optical control and ion‐irradiated silicon provides unprecedented concurrent control over space, time, and frequency response of metamaterial for designing frequency‐agile spatiotemporal modulators, active beamforming, and low‐power frequency converters for the next generation terahertz wireless communications. Abstract : Photoexcitation of ion‐irradiated silicon substrate hosting an electrically reconfigurable microelectromechanical‐system‐based metamaterial shows ultrafast terahertz resonance modulation with a large spectral tunability. The proposed approach of integrating complementing technologies of femtosecond optical control, ion‐irradiated semiconductor, and microelectromechanical systems with metamaterials provides a perfect pathway for multidimensional manipulation of terahertz waves.